Assessment of Oral Health and Treatment Needs in Population with Visual Impairment - Abarna Jawahar; G Maragathavalli (Wolters Kluwer Medknow Publications, 2022)
Background: Visually impaired individuals when compared to healthy have poor oral health status as they cannot visualize the plaque deposits on the tooth surface, leading to poor understanding of the importance of oral hygiene which results in development of dental caries as well as inflammatory disease of the periodontium and loss of tooth structure. Aim: The study aims to assess the oral health and treatment needs of patients with visual impairment using WHO Oral Health Assessment form for adults 2013. Materials and Methods: A cross-sectional study was conducted on 207 visually impaired patients who visited the special care dentistry department, a unit of Oral Medicine and Radiology in a private dental college & hospital and a private blind institute. WHO Oral Health Assessment form was filled after oral examination was done using Type III clinical examination. Statistical Analysis: Descriptive analysis was used to describe the frequencies and percentages. Chi-square test was used to determine statistical significance. Results and Conclusion: Dental caries were present in 129 (62.3%) study participants. Oral mucosal lesion was prevalent in 14% of the study population. 146 (71%) participants required prompt dental treatment such as scaling, restorations, extractions, 58 (28%) participants required immediate dental treatment due to presence of pain or infection of dental origin such as advanced dental caries, periapical abscess and OPMD. Only 3 (1%) participants out of 207 did not require any dental treatment. The findings of the study suggest that the dental treatment needs are high and unmet in the visually impaired population.